POSITIVISM OR NORMATIVISM ECONOMICS: An Appraisal toward Islamic Economics Methodology - M. Sholihin M. Sholihin (Turast: Jurnal Penelitian dan Pengabdian, 2014)
This paper endeavors to explore cotemporary epistemology of islamic economic schools classified into threecategories: Baqir Sadr, Mainstream and alternative schools. These mainstreams have been applying differenceapproaches and paradigms to analyze islamic economics. This study shows that islamic economics has ‘doubleparadigm’.Inthis case, paradigmis a model or frameworkfor observationand understanding, which shapesbothwhat wesee and howweunderstand it. this paradigmsareofferedbythe muslim economists and also areexertedto understand the islamic economics problemsin which the scientific problemin islamic economics istheoccurred-gapbetweentheories, normsand facts. Variousparadigmsof islamic economics — Subjectivism,Positivism,and Deterritorialism— areto understood and explained howthe gap betweennormand fact occursinislamic economics. this gap is a complex challenge that must be understoond and explained byapplying amulti-disciplinerapproach.